1994
DOI: 10.1113/expphysiol.1994.sp003807
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the vasopressin‐sensitive water permeability pathway in the toad bladder by N‐ethyl maleimide

Abstract: SUMMARYVasopressin stimulates transepithelial water flow in the toad urinary bladder. We report here that N-ethyl maleimide (NEM) (0-1 mM) produces a similar increase in osmotic water flow when applied to the mucosal surface of the tissue. NEM-induced water flow is sensitive to inhibitors of hormone-induced water flow, including serosal acidification, or exposure to quinidine or cytoskeleton-disruptive drugs. NEM-induced water flow is additive with that induced by a submaximal, but not a maximal, dose of vasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
3
6
1
Order By: Relevance
“…The response was increased when suspensions were incubated with 0.1 mM NEM (210 Ϯ 23% of control; n ϭ 6, P Ͻ 0.001, wrt control). The response to 0.1 mM NEM most closely resembled the response to AVP, in agreement with the findings of both Rasmussen et al (29) and Marples et al (23). The NEM-induced increase in the PM-to-ICV ratio was lower than that produced by 0.1 mM NEM when suspensions were treated with either 1 mM (1 mM NEM: 178 Ϯ 11% of control; n ϭ 5, P Ͻ 0.001 wrt control) or 5 mM NEM (5 mM NEM: 143 Ϯ 25% of control; n ϭ 6, P ϭ 0.05 wrt control).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The response was increased when suspensions were incubated with 0.1 mM NEM (210 Ϯ 23% of control; n ϭ 6, P Ͻ 0.001, wrt control). The response to 0.1 mM NEM most closely resembled the response to AVP, in agreement with the findings of both Rasmussen et al (29) and Marples et al (23). The NEM-induced increase in the PM-to-ICV ratio was lower than that produced by 0.1 mM NEM when suspensions were treated with either 1 mM (1 mM NEM: 178 Ϯ 11% of control; n ϭ 5, P Ͻ 0.001 wrt control) or 5 mM NEM (5 mM NEM: 143 Ϯ 25% of control; n ϭ 6, P ϭ 0.05 wrt control).…”
Section: Resultssupporting
confidence: 90%
“…This work is in agreement with previous studies in the toad urinary bladder, where NEM was shown to increase transepithelial water flow and induce the appearance of intramembranous particles thought to correspond to the water channels in this tissue (1,23,29). The response to NEM has similar characteristics to AVP-induced trafficking of AQP2, consistent with the view that NEM induces trafficking of AQP2 via activation of a process normally stimulated by AVP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations